Impacts of climate change on the discharge and glacier mass balance of the different glacierized watersheds in the Tianshan Mountains, Central Asia. Issue 1 (13th December 2017) - Xu, Min; Wu, Hao; Kang, Shichang
Abstract: The Tianshan Mountains represent an important water source for the arid and semi‐arid regions of Central Asia. The discharge and glacier mass balance (GMB) in the Tianshan Mountains are sensitive to changes in climate. In this study, the changes in temperature, precipitation, and discharge of six glacierized watersheds of Tianshan Mountains were explored using non‐parametric tests and wavelet transforms during 1957–2004. On the basis of the statistical mechanics and maximum entropy principle model, the GMB at the watershed scale were reconstructed for the study period. The discharge and GMB responses to climate change were examined in different watersheds. The results showed that regional climate warming was obvious, especially after 1996. The warming trend increased gradually from east to west, and the increase in temperature was greater on the north slope than on the south slope. The changing trends in precipitation increased from eastern region to central region, and then, the trend decreased in the western region, although the value was higher than that in the eastern region. The discharge presented significant periods of 2.7–5.4 years and increased from east to west. Significant periodicity indicated that the discharge in the different watersheds exhibited obviously different patterns. The GMB losses were larger in south and east than in north. The large glaciers had more stable interannual variations in discharge, and large fluctuations in discharge will be observed as the glacier areas shrink. Precipitation was the dominant factor for discharge during the study period, although the influence of increasing temperatures on hydrological regimes should not be neglected in the long term. Systematic differences in discharge and the GMB in glacierized watersheds in response to climate change are apparent in the Tianshan Mountains.